Pengaruh Penggunaan Media Sosial Terhadap Keputusan Pembelian (Studi Kasus Produk Kecantikan Pada Mahasiswi Manajemen Informatika Sekolah Tinggi Manajemen Sukma Medan) - Arnila Asri Lubis; Robbi Rahim (INTECOMS: Journal of Information Technology and Computer Science, 2024)
The purpose of this study is to ascertain how students at Sukma Medan School of Management use social media in relation to their purchases of beauty goods. Secondary data collection is the research methodology used, and data is gathered via documentation studies. Thirty distinct groups, chosen at random, comprise the study sample. PLS SEM (Partial Least Square – Structural Equation Modelling) software is used in the quantitative descriptive data analysis methodology. The PLS approach is used in the analytic strategy, along with inner and outer model analyses. The research results indicate a positive and substantial impact of social media on consumer choices to purchase. This is evident from all tested social media variables using SmartPLS, which yield positive results. The strong R-squared value of 0.717 indicates that social media has a 71.7% influence on the purchase decision variable. Additionally, factors unrelated to the investigated variable have an impact on other aspects.